Efeitos agudos do treinamento intervalado de alta intensidade e do alongamento estático na memória de trabalho visuoespacial, desempenho matemático e variabilidade da frequência cardíaca em crianças com ansiedade matemática - DOMINGUES, Mauro Roberto de Souza (Universidade Federal do Pará, 2022)
Mathematical anxiety (MA) is a specific phobia, when faced with situations involving numbers or solving mathematical problems. Evidence has demonstrated the beneficial effects of physical exercise in reducing general anxiety and increasing cognitive performance in executive functions and mathematics in children. At the moment, we know that there are still no studies on the possible cognitive benefits and mathematical performance of exercise in children with AM. General Objective: To investigate the acute effect of High Intensity Interval Training (HIIT) and Static Stretching (AE) on Visuospatial Working Memory (MTV), Mathematical Arithmetic Performance (MDT) and Heart Rate Variability (HRV) in school children from 9 to 12 years with math anxiety. Methodological procedures: The Elementary Mathematical Anxiety Scale (MARS-E) was used to classify children into high and low MA. Then, through a randomized crossover trial, different parameters: MTV, TDM and HRV were monitored before and after a HIIT or AE session, with 64 schoolchildren (33 female), from the public school system in the city of Belém- SHOVEL. Data were analyzed by estimation statistics for confidence interval, effect size and significance (p ≤ 0.05). Results: After HIIT, there was an improvement in MTV performance in the group of children with low AM (d= 0.426, p ≤ 0.05) and improvement in MDT for children with low AM (d= 0.217, p ≤ 0.05) and with high AM (d= 0.194, p ≤ 0.05). A similar result in the improvement of MDD was observed after performing an AE session in the group with low AM (d= 0.19, p ≤ 0.05) and with high AM (d= 0.209, p ≤ 0.05). The nonlinear HRV results showed that both children with low MA (d= 0.574, p ≤ 0.05) and high MA (d= 0.673, p ≤ 0.01) showed an increase in SampEn in the post-EA condition during the realization of TDM. Conclusion: HIIT may improve executive function for less anxious children, but not AE. Performing HIIT and AE exercises can provide conditions for children to improve math performance. The AE proved to be an important candidate to increase the complexity of HRV, contributing to the improvement of mathematical performance. The findings of this research point to promising paths to the need to include physical exercise in the daily school life of children with mathematical anxiety, in order to promote improvements in both mental health, cognitive level and school performance.